Tasks Implemented by Internal Auditors when Developing and Executing Business Continuity and Recovery Plan to Face the COVID-19 crisis (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The current research aimed to identify the tasks performed by the internal auditors when developing a business continuity plan to face the COVID-19 crisis. It also aims to identify the recovery and resuming plan to the business environment. The research followed the descriptive survey to find out the views of 34 internal auditors at various functional levels in the Kingdom of Saudi Arabia. Spreadsheets (Excel) were used to analyze the data collected by a questionnaire which composed of 43 statements, covering the tasks that the internal auditors can perform to face the COVID-19 crisis. Results revealed that the tasks performed by the internal auditors when developing a business continuity plan to face the COVID-19 crisis is to ensure that the plan meets the instructions issued by the government, the Ministry of Health and the World Health Organization, and they performed some tasks remotely before the crisis took place. The most apparent tasks performed by the internal auditors when implementing the business continuity work we're carrying out the tasks using some technological audit devices and recent apps to overcome new working conditions. Other tasks were performed were to participate in the provision of emergency services outside the scope of their work at the request of executive departments and to make major modifications to the risk-based internal audit plan, aiming at evaluating new activities and covering aspects of risk during the COVID-19 crisis. To recover from the COVID-19 crisis and return to the business environment, the internal auditors involved in evaluating the commitment to implement the precautionary measures and recommend following-up alternative procedures for some departments to restore business after the negative impact of organizations resources.